Safety and effectiveness of oral blonanserin for schizophrenia: A review of Japanese post-marketing surveillances - Yoshifumi Inoue; Kimiko Tsuchimori; Hiroshi Nakamura (Elsevier, 2021)
Schizophrenia significantly limits social functioning with positive and negative symptoms and cognitive dysfunction. Blonanserin (LONASEN®), a novel second-generation antipsychotic approved for treating schizophrenia in Japan in 2008, reportedly shows beneficial effects on cognitive function as well as positive and negative symptoms, with potential for improving social functioning. To understand the safety and effectiveness of blonanserin in the real clinical practice, five Japanese post-marketing surveillances have been conducted and published to date. In this article, we reviewed all the Japanese post-marketing surveillances and discussed the clinical usefulness of blonanserin in patients with schizophrenia having diverse clinical characteristics. Adverse drug reactions, such as akathisia and extrapyramidal symptoms, were common in all surveillances. However, those specific to second-generation antipsychotics, such as weight gain and abnormalities in glycometabolism or lipid metabolism, were rarely observed. In addition, no adverse drug reactions apart from clinical trial results were found. Brief Psychiatric Rating Scale total scores in all surveillances significantly lowered at the last evaluation than at baseline. These results were consistent through 1-year of treatment, suggesting that effectiveness is maintained even after long-term use. In conclusion, blonanserin is considered a beneficial drug in real clinical practice for patients with schizophrenia having diverse characteristics.